epoxy resin composition

JP7943580B2Active Publication Date: 2026-10-30SHIN ETSU CHEMICAL CO LTD +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2022186143
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-11-22
Publication Date
2026-10-30
Estimated Expiration
2042-11-22

AI Technical Summary

Benefits of technology

【0030】 本発明は、ポリオルガノシロキサンを含むエポキシ樹脂組成物に関するものである。さらに詳しくは、両末端にエポキシ基を有し、主鎖にウレタン結合を有するポリオルガノシロキサン、及び両末端にエポキシ基を有し、主鎖にメソゲン基を有するポリオルガノシロキサンを含むエポキシ樹脂組成物に関するものである。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007943580000001
    Figure 0007943580000001
  • Figure 0007943580000002
    Figure 0007943580000002
  • Figure 0007943580000003
    Figure 0007943580000003
Patent Text Reader

Abstract

To provide an epoxy resin composition containing polyorganosiloxane.SOLUTION: An epoxy resin composition comprises (A) an epoxy resin having two or more epoxy groups per molecule, (B) urethane bond-containing polyorganosiloxane represented by a formula (1), (C) mesogen group-containing polyorganosiloxane represented by a formula (2), and (D) an epoxy resin curing agent.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to epoxy resin compositions. [Background technology]

[0002] Epoxy resins are used in a variety of fields due to their excellent mechanical strength, electrical insulation, heat resistance, chemical resistance, water resistance, low shrinkage, and adhesive properties. In recent years, performance requirements for epoxy resins have increased, and development is underway to address the issue of low toughness, which is a challenge for epoxy resins (Patent Documents 1-4).

[0003] Epoxy-modified silicones are polyorganosiloxanes containing epoxy groups and are used in applications such as resin modifiers, fiber treatment agents, and paint additives, taking advantage of the reactivity of the epoxy groups. While they are also expected to impart flexibility to epoxy resins, they have a drawback: poor compatibility with other polar compounds such as curing agents, leading to separation.

[0004] Patent Document 5 describes a silicone having a urethane bond with epoxy groups introduced at both ends. In its examples, it is reported that when mixed with a bisphenol A type epoxy resin, a transparent solution is obtained, and a cured product is obtained by reaction with a curing agent. However, adding this silicone lowers the glass transition temperature (Tg) of the epoxy resin itself, which leads to a problem of deteriorating heat resistance.

[0005] Patent document 6 discloses an epoxy resin having mesogenic groups, which is reported to have excellent workability and superior mechanical, thermal, and chemical properties. However, it was unclear how these properties would change when the aforementioned epoxy resin was mixed with general epoxy resins such as bisphenol-type epoxy resins. [Prior art documents] [Patent Documents]

[0006] [Patent Document 1] Japanese Patent Publication No. 2008-239890 [Patent Document 2] Special Publication No. 2014-505761 [Patent Document 3] Special Publication No. 2017-536440 [Patent Document 4] International Publication No. 2018 / 008741 [Patent Document 5] Japanese Patent Publication No. 1986-228015 [Patent Document 6] Japanese Patent Publication No. 2008-214599 [Overview of the project] [Problems that the invention aims to solve]

[0007] This invention has been made in view of these circumstances, and aims to provide an epoxy resin composition containing a polyorganosiloxane. [Means for solving the problem]

[0008] To solve the above problems, the present invention provides an epoxy resin composition, (A) Epoxy resin containing two or more epoxy groups in one molecule, (B) Polyorganosiloxane containing urethane bonds represented by the following formula (1), [ka] (In the above formula (1), R 1 (where n is an integer from 0 to 100 and m is from 1 to 10.) (C) A mesogenic group-containing polyorganosiloxane represented by the following formula (2),

Chemical Formula

Chemical Formula

Chemical Formula

[0009] Such an epoxy resin composition will be an epoxy resin composition containing polyorganosiloxane with excellent various properties.

[0010] Further, in the present invention, it is preferable that the content of the component (B) is 1 to 20 parts by mass and the content of the component (C) is 1 to 20 parts by mass relative to 100 parts by mass of the aforementioned component (A).

[0011] With such an epoxy resin composition, sufficient strength and adhesive force as a cured product of the epoxy resin can be obtained. In addition, since the decrease in Tg can be suppressed, high heat resistance can be maintained.

[0012] Furthermore, in the present invention, it is preferable that the number-average molecular weight of component (B) in terms of polystyrene standard substances is 500 to 100,000.

[0013] With such an epoxy resin composition, the size of the structures constituting the island structures in the sea-island structure does not become too large, and microphase separation can be formed. Furthermore, the size of the island structures can be controlled by selecting the number-average molecular weight within this range.

[0014] Furthermore, in the present invention, it is preferable that the epoxy equivalent (g / mol) of component (B) is 300 to 5,000 g / mol.

[0015] With such an epoxy resin composition, the size of the structures constituting the island structures in a sea-island structure does not become excessively large, and microphase separation can be formed. Furthermore, the size of the island structures can be controlled by selecting the epoxy equivalent within this range.

[0016] Furthermore, in the present invention, it is preferable that component (B) contains hexamethylcyclotrisiloxane (D3), octamethylcyclotetrasiloxane (D4), decamethylcyclopentasiloxane (D5), and dodecamethylcyclohexasiloxane (D6) in a total amount of 3,000 ppm or less.

[0017] By reducing these cyclic low-molecular-weight siloxanes, it is possible to avoid a decrease in adhesion due to the bleed-out of low-molecular-weight components onto the cured surface, as well as contamination of the surrounding environment due to the volatilization of low-molecular-weight components.

[0018] Furthermore, in the present invention, it is preferable that the number-average molecular weight of component (C) in terms of polystyrene standard substances is 500 to 100,000.

[0019] With this molecular weight, the epoxy groups at both ends react with the curing agent, resulting in a molecular weight sufficient to obtain a cured product.

[0020] Furthermore, in the present invention, it is preferable that the epoxy equivalent (g / mol) of component (C) is 300 to 5,000 g / mol.

[0021] With such epoxy equivalents, the epoxy groups at both ends are ( D ) It reacts with the epoxy resin curing agent to form a sufficient quantity to obtain a cured product with good physical properties.

[0022] Furthermore, in the present invention, it is preferable that component (C) contains hexamethylcyclotrisiloxane (D3), octamethylcyclotetrasiloxane (D4), decamethylcyclopentasiloxane (D5), and dodecamethylcyclohexasiloxane (D6) in a total amount of 3,000 ppm or less.

[0023] By reducing these cyclic low-molecular-weight siloxanes, it is possible to avoid a decrease in adhesion due to the bleed-out of low-molecular-weight components onto the cured surface, as well as contamination of the surrounding environment due to the volatilization of low-molecular-weight components.

[0024] Furthermore, in the present invention, it is preferable that the epoxy resin (A) is a bisphenol-type epoxy resin.

[0025] Such an epoxy resin composition can enhance the properties of various selected bisphenol-type epoxy resins, resulting in an epoxy resin composition that can increase both elongation properties and tensile shear strength compared to using bisphenol-type epoxy resin alone.

[0026] Furthermore, in the present invention, it is preferable that the epoxy resin curing agent (D) is an amine-based curing agent.

[0027] Such epoxy resin compositions can be used to obtain good curing properties.

[0028] Furthermore, in the present invention, it is preferable that (E) a filler is further included.

[0029] Such epoxy resin compositions can reinforce mechanical strength. [Effects of the Invention]

[0030] The present invention relates to epoxy resin compositions containing polyorganosiloxanes. More specifically, the present invention relates to epoxy resin compositions containing polyorganosiloxanes having epoxy groups at both ends and urethane bonds in the main chain, and polyorganosiloxanes having epoxy groups at both ends and mesogenic groups in the main chain.

[0031] The epoxy resin composition of the present invention, with its predetermined structure and formulation, disperses without phase separation when curing, improves toughness without reducing the heat resistance of the cured product, and exhibits good adhesive strength when cured products are made between substrates, thus making it highly useful. Furthermore, by reducing the amount of low-molecular-weight cyclic siloxanes, it is possible to prevent accumulation on equipment and malfunctions of equipment due to their volatilization and diffusion during curing. [Modes for carrying out the invention]

[0032] As mentioned above, there was a need for the development of epoxy resin compositions containing polyorganosiloxanes with desirable properties.

[0033] As a result of diligent research into the above-mentioned problems, the inventors of the present invention have found that an epoxy resin composition comprising (A) epoxy resin, (B) urethane bond-containing polyorganosiloxane, (C) mesogenic group-containing polyorganosiloxane, and (D) epoxy resin curing agent can solve the above-mentioned problems, and have completed the present invention.

[0034] That is, the present invention relates to an epoxy resin composition, (A) Epoxy resin containing two or more epoxy groups in one molecule, (B) Polyorganosiloxane containing urethane bonds represented by the following formula (1), [ka] (In the aforementioned formula (1), R 1 each independently represent a group selected from an alkyl group having 1 to 12 carbon atoms, an aryl group having 6 to 12 carbon atoms, and an aralkyl group having 7 to 12 carbon atoms, or a hydroxyl group; X each independently represent a divalent alkylene group having 1 to 10 carbon atoms; Y each independently represent a group selected from an alkylene group which may have an ether bond and has 5 to 30 carbon atoms, an arylene group having 6 to 30 carbon atoms, and an aralkylene group having 7 to 30 carbon atoms; Z each independently represent an alkylene group which may have an ether bond and has 1 to 20 carbon atoms; n is an integer of 0 to 100, and m is 1 to 10.) (C) A mesogenic group-containing polyorganosiloxane represented by the following formula (2),

Chemical Formula

Chemical Formula

Chemical Formula

[0035] [Epoxy Resin Composition] The epoxy resin composition of the present invention is an epoxy resin composition comprising (A) an epoxy resin, (B) a urethane bond-containing polyorganosiloxane, (C) a mesogenic group-containing polyorganosiloxane, and (D) an epoxy resin curing agent. The present invention will be described in detail below, but the present invention is not limited to these descriptions.

[0036] [(A) Epoxy resin] The epoxy resin (A) in the present invention contains two or more epoxy groups in one molecule. This epoxy resin can be a known epoxy resin and is not particularly limited, but examples include bisphenol type epoxy resins such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, and bisphenol S type epoxy resin; alicyclic epoxy resins such as dicyclopentadiene type epoxy resin and 3,4-epoxycyclohexenylmethyl-3',4'-epoxycyclohexene carboxylate; polyfunctional phenol type epoxy resins such as resorcinol type epoxy resin; stilbene type epoxy resin, triazine skeleton-containing epoxy resin, fluorene skeleton-containing epoxy resin, triphenolalkane type epoxy resin, biphenyl type epoxy resin, xylylene type epoxy resin, biphenylaralkyl type epoxy resin, naphthalene type epoxy resin, and diglycidyl ether compounds of polycyclic aromatics such as anthracene. These can be used individually or in combination of two or more. Preferably, it is a bisphenol type epoxy resin. In this invention, components (A), (B), and (C) are all different.

[0037] The epoxy equivalent of the epoxy resin in (A) is not particularly limited, but from the viewpoint of pot life after mixing and strength of the cured product, it is preferably 50 to 5,000 g / eq, and more preferably 75 to 2,500 g / eq, when calculated on a solid content basis.

[0038] The viscosity of the epoxy resin (A) is not particularly limited, but it is preferably liquid at 25°C and has a viscosity of 10 to 100,000 mPa·s, preferably 20 to 50,000 mPa·s. The viscosity is measured using a B-type viscometer.

[0039] [(B) Polyorganosiloxane containing urethane bonds] In the present invention, (B) the urethane bond-containing polyorganosiloxane is represented by the following formula (1). [ka] (In the above formula (1), R 1 (where n is an integer from 0 to 100 and m is from 1 to 10.)

[0040] In equation (1), R 1 These groups are independently selected from alkyl groups having 1 to 12 carbon atoms, preferably 1 to 8 carbon atoms, aryl groups having 6 to 12 carbon atoms, preferably 6 to 9 carbon atoms, and aralkyl groups having 7 to 12 carbon atoms, preferably 7 to 10 carbon atoms, or hydroxyl groups. Specific examples include linear or branched alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, s-butyl, t-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, 2-ethylhexyl, n-nonyl, and n-decyl groups; cycloalkyl groups such as cyclohexyl; aryl groups such as phenyl and naphthyl; and aralkyl groups such as benzyl. Among these, methyl or phenyl groups are preferred.

[0041] In formula (1), X is an alkylene group having 1 to 10 carbon atoms, preferably 1 to 8 carbon atoms, independently of each other.

[0042] Specific examples of alkylene groups having 1 to 10 carbon atoms include methylene, ethylene, propylene, n-hexylene, and n-octylene groups. Methylene is preferred.

[0043] In formula (1), Y is a group independently selected from alkylene groups having 5 to 30 carbon atoms, arylene groups having 6 to 30 carbon atoms, and aralkylene groups having 7 to 30 carbon atoms.

[0044] Alkylene groups having 5 to 30 carbon atoms can be linear, branched, or cyclic. Specific examples include linear or branched alkylene groups such as n-pentylene, n-hexylene, n-heptylene, n-octylene, 2-ethylhexylene, n-decylene, n-undecylene, n-dodecylene, n-tridecylene, n-tetradecylene, n-pentadecylene, n-hexadecylene, n-heptadecylene, n-octadecylene, n-nonadesilene, and n-eicosanylene.

[0045] Furthermore, the alkylene group may have one or more ether bonds in the middle of the molecular chain. Specifically, it may be a group containing an ether bond, such as an ethyleneoxy group, a propyleneoxy group, or a butyleneoxy group, and may have multiple ether bonds.

[0046] Examples of arylene groups having 6 to 30 carbon atoms include o-phenylene group, m-phenylene group, p-phenylene group, 3,5-trylene group, 2,4-trylene group, 2,6-trylene group, 1,2-naphthylene group, 1,8-naphthylene group, 2,3-naphthylene group, 4,4'-biphenylene group, and 4,4'-methylenebisphenyl group.

[0047] Examples of aralkylene groups having 7 to 30 carbon atoms include o-xylylene group, m-xylylene group, p-xylylene group, and 1,3-phenylenebis(2-propyl) group.

[0048] The following groups are preferred as Y. The dotted lines indicate the bonding sites with the nitrogen atom of the urethane bond in formula (1), and by convention, the hydrogen atom is omitted. [ka]

[0049] In formula (1), Z is an alkylene group having 1 to 20 carbon atoms, preferably 3 to 10 carbon atoms, independently of each other. One or more ether bonds may be interposed in the alkylene chain having 1 to 20 carbon atoms. Preferably, it is a propylene group (-CH2CH2CH2-) or an ethyleneoxypropylene group (*-CH2CH2OCH2CH2CH2-). Here, * indicates a bond with the oxygen atom of the urethane bond in formula (1).

[0050] In equation (1), n ​​represents an integer between 0 and 100. Preferably, n is an integer between 0 and 60.

[0051] In formula (1), m represents the average degree of polymerization, and m is between 1 and 10, preferably 1 or 2.

[0052] In the present invention, the (B) urethane bond-containing polyorganosiloxane preferably has a number average molecular weight of 500 to 100,000, more preferably 500 to 50,000, and even more preferably 500 to 20,000. Within this range, the epoxy groups at both ends react with the curing agent to obtain a molecular weight sufficient to yield a cured product. The number average molecular weight refers to the number average molecular weight in terms of polystyrene standard substance measured by gel permeation chromatography (GPC) under the following measurement conditions.

[0053] [Measurement conditions] Developing solvent: Tetrahydrofuran (THF) Flow rate: 0.6mL / min Detector: Differential refractive index detector (RI) Column: TSK Guardcolumn SuperH-H TSKgel SuperHM-N(6.0mmI.D.×15cm×1) TSKgel SuperH2500(6.0mmI.D.×15cm×1) (All manufactured by Tosoh Corporation) Column temperature: 40℃ Sample injection volume: 50 μL (THF solution with a concentration of 0.3% by mass)

[0054] In the present invention, the (B) urethane bond-containing polyorganosiloxane preferably has an epoxy equivalent (g / mol) of 300 to 5,000 g / mol, and more preferably 400 to 2,500 g / mol. Within this range, the epoxy groups at both ends react with the curing agent, resulting in a sufficient amount to obtain a cured product with good physical properties. The epoxy equivalent (g / mol) can be calculated by adding hydrochloric acid to a predetermined mass of sample dissolved in 1,4-dioxane and back titrating with an aqueous sodium hydroxide solution.

[0055] With regard to low molecular weight cyclic siloxanes, various problems may occur, as described in International Publication No. 2016 / 111104, etc., and it is preferable to reduce their presence. In the (B) urethane bond-containing polyorganosiloxane represented by formula (1), preferably one containing hexamethylcyclotrisiloxane (D3), octamethylcyclotetrasiloxane (D4), decamethylcyclopentasiloxane (D5), and dodecamethylcyclohexasiloxane (D6) in a total amount of 3,000 ppm or less, more preferably 2,000 ppm or less, and even more preferably 1,000 ppm or less can be used.

[0056] The amount of the above low molecular weight cyclic siloxanes (D3-D6) can be quantified by gas chromatography (GC) using a sample obtained by extracting and diluting the (B) urethane bond-containing polyorganosiloxane represented by formula (1) with an organic solvent.

[0057] [(C) Mesogenic group-containing polyorganosiloxane] The mesogenic group-containing polyorganosiloxane in the present invention is represented by the following formula (2). [ka] (In the above formula (2), R 1 R independently represents a group selected from an alkyl group having 1 to 12 carbon atoms, an aryl group having 6 to 12 carbon atoms, and an aralkyl group having 7 to 12 carbon atoms, or a hydroxyl group, p represents a repeating unit of the siloxane structure and is an integer from 0 to 100, and R 2 These independently represent either equation (3) or equation (4) below.

[0058] In equation (2), R 1 These are independent of each other and are the same as those listed in formula (1) above.

[0059] p represents the number of repeating units in the siloxane structure, and is an integer from 0 to 100, preferably from 0 to 40, more preferably from 0 to 10, with p=1 being even more preferable.

[0060] In equation (2), R 2 These are independently given by equation (3) or (4) below. [ka] [ka] (In equations (3) and (4) above, R 3 and R 4 A, B, and C independently represent a hydrogen atom or a monovalent hydrocarbon group having 1 to 10 carbon atoms; L is a linking group to formula (2) and is a divalent hydrocarbon group having 1 to 12 carbon atoms; a and b represent the number of substituents on the phenyl group in formulas (3) and (4) and are integers from 0 to 4; and G is glycidyl Lu group (That is the case.)

[0061] In equations (3) and (4), R 3 and R 4These independently represent a hydrogen atom or a monovalent hydrocarbon group having 1 to 10 carbon atoms.

[0062] The monovalent hydrocarbon group having 1 to 10 carbon atoms is preferably a group selected from alkyl groups having 1 to 10 carbon atoms, aryl groups having 6 to 10 carbon atoms, or aralkyl groups having 7 to 10 carbon atoms. Specific examples of such groups are similar to those exemplified in formula (1) above.

[0063] a and b represent the number of substituents on the phenyl group in formulas (3) and (4), and are integers between 0 and 4.

[0064] In formulas (3) and (4), G is a glycidyl group.

[0065] In formulas (3) and (4), L is a linking group with formula (2), and is a divalent hydrocarbon group having 1 to 12 carbon atoms.

[0066] Examples of divalent hydrocarbon groups include alkylene groups with 1 to 12 carbon atoms, arylene groups with 6 to 12 carbon atoms, and aralkylene groups with 7 to 12 carbon atoms.

[0067] The alkylene group having 1 to 12 carbon atoms may be linear, branched, or cyclic. Specific examples include linear or branched alkylene groups such as n-pentylene, n-hexylene, n-heptylene, n-octylene, 2-ethylhexylene, n-decylene, n-undecylene, and n-dodecylene.

[0068] Furthermore, the alkylene group may have one or more ether bonds in the middle of the molecular chain. Specifically, it may be a group containing an ether bond, such as an ethyleneoxy group, a propyleneoxy group, or a butyleneoxy group, and may have multiple ether bonds.

[0069] Examples of arylene groups having 6 to 12 carbon atoms include o-phenylene group, m-phenylene group, p-phenylene group, 3,5-trylene group, 2,4-trylene group, 2,6-trylene group, 1,2-naphthylene group, 1,8-naphthylene group, 2,3-naphthylene group, and 4,4'-biphenylene group.

[0070] Examples of aralkylene groups having 7 to 12 carbon atoms include o-xylylene groups, m-xylylene groups, and p-xylylene groups.

[0071] R in equation (2) 2 More preferably, it is formula (5). [ka]

[0072] c represents the number of carbon atoms in the linking group with the siloxane skeleton in formula (5), and is an integer from 0 to 6, preferably c=1.

[0073] The dotted line indicates the connection point with equation (2).

[0074] In the present invention, the (C) mesogenic group-containing polyorganosiloxane preferably has a number-average molecular weight of 500 to 100,000, more preferably 500 to 50,000, and even more preferably 500 to 20,000. Within this range, the epoxy groups at both ends react with the curing agent to obtain a molecular weight sufficient to yield a cured product. The number-average molecular weight is the same as described above.

[0075] In the present invention, the (C) mesogenic group-containing polyorganosiloxane preferably has an epoxy equivalent (g / mol) of 300 to 5,000 g / mol, and more preferably 400 to 2,500 g / mol. Within this range, the epoxy groups at both ends react with the (D) epoxy resin curing agent described later, resulting in a sufficient amount to obtain a cured product with good physical properties. The epoxy equivalent (g / mol) can be calculated by adding hydrochloric acid to a predetermined mass of sample dissolved in 1,4-dioxane and back titrating with an aqueous sodium hydroxide solution.

[0076] With regard to low molecular weight cyclic siloxanes, various problems may occur, as described in International Publication No. 2016 / 111104, etc., and it is preferable to reduce their amount. Component (C) preferably contains hexamethylcyclotrisiloxane (D3), octamethylcyclotetrasiloxane (D4), decamethylcyclopentasiloxane (D5), and dodecamethylcyclohexasiloxane (D6) in a total amount greater than 0 ppm and 3,000 ppm or less, more preferably 0.1 to 2,000 ppm, and even more preferably 0.1 to 1,000 ppm.

[0077] The amounts of the above-mentioned low molecular weight cyclic siloxanes (D3-D6) are values ​​quantified by gas chromatography (GC) using samples obtained by extracting and diluting component (C) with an organic solvent. Furthermore, "greater than 0 ppm" means that if even a small peak is detected when quantified by the above method, it is considered "greater than 0 ppm".

[0078] In the present invention, when component (A) is 100 parts by mass, component (B) is preferably 1 to 20 parts by mass, and more preferably 10 to 20 parts by mass. Similarly, component (C) is preferably 1 to 20 parts by mass, and more preferably 1 to 10 parts by mass. If the mass amounts of components (B) and (C) are within this range, sufficient strength and adhesiveness as a cured epoxy resin can be obtained. In addition, since the decrease in Tg can be suppressed, high heat resistance can be maintained.

[0079] [(D) Epoxy resin hardener] In the present invention, (D) epoxy resin curing agent can be any known curing agent capable of reacting with and curing epoxy resin. This curing agent is added to react the reactive functional groups (amino groups, phenolic hydroxyl groups, acid anhydride groups, mercapto groups, etc.) in the molecule of the curing agent with the epoxy groups in components (A), (B), and (C) to form a cured product with a three-dimensional crosslinked structure.

[0080] (D) Examples of components include amine-based curing agents, phenol-based curing agents, acid anhydride-based curing agents, thiol-based curing agents, etc.

[0081] Among these, amine-based curing agents are preferred. Examples of amine-based curing agents include aromatic polyamines, aliphatic polyamines, polyamidoamines, and polyether polyamines. Aromatic polyamines are even more preferred.

[0082] Examples of aromatic polyamines include the compounds shown in the following formulas (I) to (IV). [ka] (In formulas (I) to (IV), R is independently a hydrogen atom or a monovalent alkyl group having 1 to 6 carbon atoms, and R' is independently a hydrogen atom, a monovalent alkyl group having 1 to 12 carbon atoms, a phenyl group, or an aminophenyl group, and two R' groups may bond together to form a ring structure with the carbon atom to which they are bonded.)

[0083] Specific examples of aromatic polyamines include aromatic diaminodiphenylmethane compounds such as 4,4'-diaminodiphenylmethane, 3,3'-diethyl-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane, and 3,3',5,5'-tetraethyl-4,4'-diaminodiphenylmethane, as well as 2,4-diaminotoluene, 1,4-diaminobenzene, and 1,3-diaminobenzene. These can be used individually or in combination of two or more.

[0084] In the present invention, when component (A) is 100 parts by mass, component (D) is preferably 1 to 20 parts by mass, and more preferably 1 to 10 parts by mass. If the amount of component (D) is 20 parts by mass or less, sufficient strength and adhesiveness as a cured epoxy resin can be obtained. In addition, since the decrease in Tg can be suppressed, high heat resistance can be maintained. If the amount of component (D) is 1 part by mass or more, the desired effect of adding component (D) can be sufficiently obtained.

[0085] [Other ingredients] The epoxy resin composition of the present invention may further include (E) a filler. Examples of fillers include silicas such as fused silica, crystalline silica, and cristobalite, and metal oxides such as aluminum oxide, titanium oxide, and magnesium oxide, and may be used individually or in combination of two or more. Among these, silicas are preferred from the viewpoint of availability and quality stability. The average particle size is preferably 0.1 to 50 μm and can be selected according to the application. The average particle size may be the volume-average particle size measured by, for example, laser diffraction.

[0086] The above-mentioned filler is preferably pre-surface-treated with a coupling agent such as a silane coupling agent. However, there are no particular restrictions on the amount of coupling agent used for surface treatment or the surface treatment method.

[0087] The epoxy resin composition of the present invention may contain other additives as needed, in accordance with the objectives of the present invention. Examples of additives include reactive diluents, curing accelerators, flame retardants, ion trapping agents, antioxidants, adhesion aids, colorants, and coupling agents.

[0088] The present invention provides a method for producing an epoxy resin composition, for example, by simultaneously mixing, stirring, dissolving, and dispersing components (A), (B), (C), and (D) while performing heat treatment. Alternatively, the composition can be obtained by mixing, stirring, dissolving, and dispersing components (A), (B), (C), or (D) separately while performing heat treatment. Preferably, a composition in which component (B) is well dispersed can be obtained by mixing, stirring, dissolving, and dispersing components (B), (C), and (D) while performing heat treatment, and then adding component (A).

[0089] Additionally, component (E) and / or other additives may be added as needed. Components (A), (B), (C), and (D) may be mixed, stirred, dissolved, and dispersed while being heated simultaneously or separately. Alternatively, components (B), (C), and (D) may be mixed, stirred, dissolved, and dispersed while being heated, and then component (E) and / or other additives may be added simultaneously with component (A).

[0090] The curing conditions for the epoxy resin composition in the present invention are not particularly limited, but for example, heating at a temperature of 60 to 200°C, preferably 80 to 180°C, for 30 minutes to 10 hours, preferably 1 to 5 hours is recommended. Alternatively, to ensure efficient reaction, heating may be carried out in 1 to 5 stages, starting from a lower temperature and progressing to a higher temperature for the aforementioned durations. [Examples]

[0091] The present invention will be specifically described below using examples, comparative examples, and synthesis examples, but the present invention is not limited to these.

[0092] Bisphenol A type epoxy resin: Mitsubishi Chemical Corporation, jER828EL (Epoxy equivalent: 186 g / mol, Viscosity: 13,000 mPa·s) (Hereafter referred to as DGEBA.) Amine-based curing agent: 4,4'-diaminodiphenylmethane, manufactured by Tokyo Chemical Industry Co., Ltd. (NH equivalent: 49.6g / mol) (Hereafter referred to as DDM.)

[0093] [Synthesis Example 1] Method for synthesizing SU epoxy resin 91.95 g (0.827 mol NCO) of isophorone diisocyanate was placed in a 500 mL separable flask, and a mechanical stirrer, stirring blade, Liebig reflux tube, nitrogen gas inlet, and thermometer were attached, and nitrogen gas was introduced. Next, 0.32 g (0.1 mass%) of the catalyst K-KAT XK-640 (Kusumoto Chemical Co., Ltd., bismuth carboxylate, 18% bismuth content) was added, and the temperature was raised until the internal temperature reached 60°C. To this, 200.00 g (0.413 mol OH, NCO / OH=2.0) of 3-(2-hydroxyethoxy)propyldimethylsiloxy-terminated polydimethylsiloxane (n=8, OH value 116 mgKOH / g) with D3 at 64 ppm, D4 at 59 ppm, D5 at 23 ppm, and D6 at 226 ppm was added over 30 minutes using a 300 mL dropping funnel, and then aged at 70°C for 3 hours. Subsequently, 30.80 g (0.415 mol) of glycidol was added and aged at 70°C for 2 hours to obtain 319.17 g of a colorless, slightly turbid, viscous liquid. Since NCO / OH=2.0, m is 1. Low molecular weight cyclic siloxanes were extracted from 1 g of sample with 10 mL of hexane using tetradecane as an internal standard, and measured by GC. The total amount of D3-D6 was 305 ppm (D3: 54 ppm, D4: 52 ppm, D5: 16 ppm, D6: 183 ppm).

[0094] [Synthesis Example 2] Method for synthesizing SM epoxy resin In a glass reactor, 360 mL of ethanol, 17.9 g (0.164 mol) of p-aminophenol, 20 g (0.164 mol) of 4-allyloxybenzaldehyde, and a small amount of zinc chloride were added. After reacting in an oil bath at 60°C for 4 hours, the mixture was allowed to stand in a refrigerator for 2 hours. The precipitated crystals were filtered off to obtain 27 g of 4-((4-allyloxy)benzylideneamino)phenol. Next, 7 g (0.033 mol) of the obtained 4-((4-allyloxy)benzylideneamino)phenol, 5 mL of dimethyl sulfoxide, 37 g of epichlorohydrin (0.394 mol), and a small amount of tetra-n-butylammonium chloride were added to a 500 ml separable flask, and the mixture was reacted at 60°C for 2 hours. Then, 3.16 g (0.04 mol) of 50% sodium hydroxide aqueous solution was added dropwise over 1 hour, and the mixture was reacted for a further 3 hours. The resulting solution was cooled, the precipitated crystals were filtered off, thoroughly washed with distilled water, and dried to obtain 3.9 g of 4-((4-allyloxy)benzylideneamino)phenol glycidyl ether. Two g (6.5 mmol) of 4-((4-allyloxy)benzylideneamino)phenol glycidyl ether was placed in a separable flask and dissolved in 40 mL of 1,4-dioxane. Then, 0.667 g (3.24 mmol) of 1,1,3,3,5,5-hexamethyltrisiloxane and 0.02 g (0.06 mmol) of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane platinum complex were added, and the mixture was heated and stirred for 6 hours with the oil bath temperature raised to 90°C. The reaction solution was cooled, the precipitated crystals were filtered off, and thoroughly washed with methanol to obtain white crystals. The amount of low molecular weight cyclic siloxanes (D3-D6) in the obtained SM epoxy resin was measured, and all were below the detection limit.

[0095] [Example 1] Degassed DGEBA, Synthesis Example 1, and Synthesis Example 2 were placed in aluminum cups and heated on a hot plate at 130°C to reduce viscosity. Subsequently, a chemical equivalent of DDM was placed in the other aluminum cup and stirred on the hot plate at the same temperature until completely melted. After that, the melted DDM was added to the previously prepared aluminum cups and stirred for 5 minutes to prepare the compositions. Subsequently, the aluminum cups containing the above composition were heated and cured in three stages: 120°C for 2 hours, 150°C for 2 hours, and then 180°C for 2 hours. The heating rate was 5°C / min. The proportions of the ingredients and the physical properties of the cured product are shown in Table 1.

[0096] [Example 2] For Synthesis Example 1, Synthesis Example 2, and the total amount of melted epoxy, chemically equivalent amounts of DDM were added to an aluminum cup and stirred on a hot plate at 140°C for 15 minutes. Subsequently, the degassed DGEBA was placed in the other aluminum cup and heated on the same hot plate to reduce its viscosity. After that, the viscosity-reduced DGEBA was added to the previously prepared aluminum cup and heated and stirred for 2 minutes to prepare the composition. Subsequently, the aluminum cups containing the above composition were heated and cured in a constant temperature bath in three stages: 120°C for 2 hours, 150°C for 2 hours, and then 180°C for 2 hours. The heating rate was 5°C / min. The proportions of the mixture and the physical properties of the cured product are shown in Table 1.

[0097] [Comparative Example 1] Degassed DGEBA was placed in an aluminum cup and heated on a hot plate at 130°C to reduce its viscosity. Next, a chemical equivalent amount of DDM was placed in the other aluminum cup and stirred on the same hot plate until completely melted. Then, the melted DDM was added to the aluminum cup containing DGEBA and stirred for 5 minutes to prepare the composition. Subsequently, the aluminum cups containing the above composition were heated and cured in a constant temperature bath in three stages: 120°C for 2 hours, 150°C for 2 hours, and then 180°C for 2 hours. The heating rate was 5°C / min. The proportions of the mixture and the physical properties of the cured product are shown in Table 1.

[0098] [Comparative Example 2] The degassed DGEBA and Synthesis Example 1 were placed in aluminum cups and heated on a hot plate at 130°C to reduce viscosity. Next, a chemical equivalent of DDM was placed in the other aluminum cup and stirred on the hot plate at the same temperature until completely melted. Then, the melted DDM was added to the previously prepared aluminum cup and stirred for 5 minutes to prepare the composition. Subsequently, the aluminum cups containing the above composition were heated and cured in three stages: 120°C for 2 hours, 150°C for 2 hours, and then 180°C for 2 hours. The heating rate was 5°C / min. The proportions of the ingredients and the physical properties of the cured product are shown in Table 1.

[0099] [Comparative Example 3] The degassed DGEBA and Synthesis Example 2 were placed in aluminum cups and heated on a hot plate at 130°C to reduce viscosity. Next, a chemical equivalent of DDM was placed in the other aluminum cup and stirred on the hot plate at the same temperature until completely melted. Then, the melted DDM was added to the previously prepared aluminum cup and stirred for 5 minutes to prepare the composition. Subsequently, the aluminum cups containing the above composition were heated and cured in three stages: 120°C for 2 hours, 150°C for 2 hours, and then 180°C for 2 hours. The heating rate was 5°C / min. The proportions of the ingredients and the physical properties of the cured product are shown in Table 1.

[0100] [Dynamic viscoelasticity measurement] The cured materials of Examples 1-2 and Comparative Examples 1-3 were cut into test specimens measuring 30 mm in length, 4.0 mm in width, and 0.40 mm in thickness. Measurements were taken using a UBM Rheogel-E40000 under the following conditions: temperature range -150 to 250°C, sinusoidal wave, heating rate 2.5°C / min, tensile mode, and frequency 10 Hz. For the obtained results, the peak top of the loss tangent tanδ, which is the loss modulus (G) / storage modulus (G'), was defined as Tg.

[0101] [Table 1]

[0102] [Examples 3-4, Comparative Examples 4-6] [Tensile shear bonding test] The mild steel plate was immersed in acetone and ultrasonically cleaned for 30 minutes. Next, the mild steel plate was polished with an electric sander fitted with #240 grit sandpaper to remove the oxide film from the surface, and then immersed in acetone and ultrasonically cleaned for 30 minutes twice. After that, a backing plate (length 25 mm x width 25 mm x thickness 1.6 mm) was attached to the mild steel plate 62.5 mm from the edge. The composition prepared in each example was then applied to the mild steel plate up to 12.5 mm from the edge, another mild steel plate was placed on top, and the two were heated at 120°C for 2 hours at 5 MPa using a hot press. After that, a weight (weight: 1,700 g, pressure: 960 Pa) was placed on the test piece in a constant temperature bath, heated at 150°C for 2 hours, then heated to 180°C at a heating rate of 5°C / min, and heated and cured at 180°C for 2 hours to prepare the test piece. After slow cooling, the test specimen was removed, and the excess resin that had seeped out from the joint was removed with a utility knife. The obtained test specimens were subjected to tensile shear bonding tests using a Shimadzu AGS-X at a head speed of 50 mm / min. Breaking strength and elongation were measured as the average value for N=5. The failure mode was confirmed visually. The compositions used for evaluation and the results of the tensile shear bonding tests are shown in Table 2.

[0103] [T-type peel test] Using aluminum foil (200 mm long x 500 mm wide x 0.05 mm thick), the composition prepared in each example was applied from the edge of the aluminum foil to a length of 170 mm, and another piece of aluminum foil was placed on top. The mixture was then heated at 120°C for 2 hours at 5 MPa using a hot press. After that, a weight (weight: 1,700 g, pressure: 960 Pa) was placed on the test specimen in a constant temperature bath, and it was heated at 150°C for 2 hours. Then, the temperature was increased to 180°C at a heating rate of 5°C / min, and the specimen was heat-cured at 180°C for 2 hours to prepare the test specimen. After slow cooling, the aluminum foil was removed and cut to a width of 25 mm to prepare the test specimen. The obtained test specimens were subjected to a T-type peel test using a Shimadzu AGS-X at a head speed of 100 mm / min. The average test force over a 150 mm section, excluding the first and last 25 mm of the test, was defined as the peel strength, and the average value for N=5 was used. The fracture mode was confirmed visually. The compositions used for evaluation and the results of the T-type peel test are listed in Table 2.

[0104] [Table 2]

[0105] Compared to the comparative example, the examples showed increased breaking strength and peel strength in tensile shear adhesion tests and T-type peel tests. This demonstrates that the epoxy resin of the present invention is effective in improving adhesion to the substrate, and thus demonstrates the usefulness of the epoxy resin composition of the present invention.

[0106] This specification includes the following embodiments. [1]: An epoxy resin composition, (A) Epoxy resin containing two or more epoxy groups in one molecule, (B) Polyorganosiloxane containing urethane bonds represented by the following formula (1), [ka] (In the above formula (1), R 1 (where n is an integer from 0 to 100 and m is from 1 to 10.) (C) A mesogenic group-containing polyorganosiloxane represented by the following formula (2), [ka] (In the above formula (2), R 1R independently represents a group selected from an alkyl group having 1 to 12 carbon atoms, an aryl group having 6 to 12 carbon atoms, and an aralkyl group having 7 to 12 carbon atoms, or a hydroxyl group, p represents a repeating unit of the siloxane structure and is an integer from 0 to 100, and R 2 These independently represent either equation (3) or equation (4) below. [ka] [ka] (In equations (3) and (4) above, R 3 and R 4 A, B, and C independently represent a hydrogen atom or a monovalent hydrocarbon group having 1 to 10 carbon atoms; L is a linking group to formula (2) and is a divalent hydrocarbon group having 1 to 12 carbon atoms; a and b represent the number of substituents on the phenyl group in formulas (3) and (4) and are integers from 0 to 4; and G is glycidyl Lu group (That is the case.) (D) Epoxy resin curing agent An epoxy resin composition characterized by containing the following: [2]: The epoxy resin composition according to [1], characterized in that it contains 1 to 20 parts by mass of component (B) and 1 to 20 parts by mass of component (C) per 100 parts by mass of component (A). [3]: The epoxy resin composition according to [1] or [2] above, characterized in that the number average molecular weight of component (B) on a polystyrene standard basis is 500 to 100,000. [4]: The epoxy resin composition according to any one of [1] to [3] above, characterized in that the epoxy equivalent (g / mol) of component (B) is 300 to 5,000 g / mol. [5]: The epoxy resin composition according to any one of [1] to [4] above, characterized in that the component (B) contains hexamethylcyclotrisiloxane (D3), octamethylcyclotetrasiloxane (D4), decamethylcyclopentasiloxane (D5), and dodecamethylcyclohexasiloxane (D6) in a total amount of 3,000 ppm or less. [6]: The epoxy resin composition according to any one of [1] to [5] above, characterized in that the number average molecular weight of component (C) on a polystyrene standard basis is 500 to 100,000. [7]: The epoxy resin composition according to any one of [1] to [6] above, characterized in that the epoxy equivalent (g / mol) of component (C) is 300 to 5,000 g / mol. [8]: The epoxy resin composition according to any one of [1] to [7] above, characterized in that the (C) component contains hexamethylcyclotrisiloxane (D3), octamethylcyclotetrasiloxane (D4), decamethylcyclopentasiloxane (D5), and dodecamethylcyclohexasiloxane (D6) in a total amount of 3,000 ppm or less. [9]: The epoxy resin composition according to any one of [1] to [8] above, characterized in that the (A) epoxy resin is a bisphenol type epoxy resin.

[10] : The epoxy resin composition according to any one of [1] to [9] above, characterized in that the (D) epoxy resin curing agent is an amine-based curing agent.

[11] : The epoxy resin composition according to any one of the above [1] to

[10] , further comprising (E) a filler.

[0107] It should be noted that the present invention is not limited to the embodiments described above. The embodiments described above are illustrative, and any configuration that is substantially identical to the technical idea described in the claims of the present invention and achieves similar effects is included within the technical scope of the present invention.

Claims

1. An epoxy resin composition, (A) Epoxy resin containing two or more epoxy groups in one molecule, (B) Polyorganosiloxane containing urethane bonds represented by the following formula (1), 【Chemistry 1】 (In formula (1) above, R 1 (where n is an integer from 0 to 100 and m is from 1 to 10.) (C) A mesogenic group-containing polyorganosiloxane represented by the following formula (2), 【Chemistry 2】 (In the above formula (2), R 1 R independently represents a group selected from an alkyl group having 1 to 12 carbon atoms, an aryl group having 6 to 12 carbon atoms, and an aralkyl group having 7 to 12 carbon atoms, or a hydroxyl group, p represents a repeating unit of the siloxane structure and is an integer from 0 to 100, 2 These independently represent either equation (3) or equation (4) below. 【Transformation 3】 【Chemistry 4】 (In formulas (3) and (4) above, R 3 and R 4 (Each of the terms independently represents a hydrogen atom or a monovalent hydrocarbon group having 1 to 10 carbon atoms; L is a linking group to formula (2) and is a divalent hydrocarbon group having 1 to 12 carbon atoms; a and b represent the number of substituents on the phenyl group in formulas (3) and (4) and are integers from 0 to 4; and G is a glycidyl group.) (D) Epoxy resin hardener An epoxy resin composition characterized by containing the following:

2. The epoxy resin composition according to claim 1, characterized in that it contains 1 to 20 parts by mass of component (B) and 1 to 20 parts by mass of component (C) per 100 parts by mass of component (A).

3. The epoxy resin composition according to claim 1, characterized in that the number average molecular weight of component (B) on a polystyrene standard basis is 500 to 100,000.

4. The epoxy resin composition according to claim 1, characterized in that the epoxy equivalent (g / mol) of component (B) is 300 to 5,000 g / mol.

5. The epoxy resin composition according to claim 1, characterized in that the component (B) contains hexamethylcyclotrisiloxane (D3), octamethylcyclotetrasiloxane (D4), decamethylcyclopentasiloxane (D5), and dodecamethylcyclohexasiloxane (D6) in a total amount of 3,000 ppm or less.

6. The epoxy resin composition according to claim 1, characterized in that the number average molecular weight of component (C) on a polystyrene standard basis is 500 to 100,000.

7. The epoxy resin composition according to claim 1, characterized in that the epoxy equivalent (g / mol) of component (C) is 300 to 5,000 g / mol.

8. The epoxy resin composition according to claim 1, characterized in that the (C) component contains hexamethylcyclotrisiloxane (D3), octamethylcyclotetrasiloxane (D4), decamethylcyclopentasiloxane (D5), and dodecamethylcyclohexasiloxane (D6) in a total amount of 3,000 ppm or less.

9. The epoxy resin composition according to claim 1, characterized in that the epoxy resin (A) is a bisphenol-type epoxy resin.

10. The epoxy resin composition according to claim 1, characterized in that the (D) epoxy resin curing agent is an amine-based curing agent.

11. The epoxy resin composition according to any one of claims 1 to 10, further characterized in that it contains (E) a filler.

Citation Information

Patent Citations

  • Epoxy resin composition

    JP1986228015A

  • Liquid crystalline epoxy resin and composition thereof

    JP2008214599A

  • Curable resin composition and automotive structural adhesive containing the same

    JP2008239890A

  • Structural epoxy resin adhesive containing chain-extended elastomer reinforcing agents capped with phenol, polyphenol, or aminophenol compounds.

    JP2014505761A

  • Epoxy resin, epoxy resin composition and method for producing epoxy resin

    JP2015048400A